2019
DOI: 10.3389/fmolb.2019.00005
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of MXD3 and Its Regulation of MXD3 Levels in Glioblastoma

Abstract: The transcription factor MXD3 is an atypical member of the MYC/MAX/MXD transcriptional network and has been previously shown to be an important regulator of cell proliferation. MXD3 has been shown to be overexpressed and to be required for medulloblastoma and acute lymphoblastic leukemia cell proliferation. In this study we leveraged datasets from The Cancer Genome Atlas to examine MXD3 across several cancers. We find that MXD3 transcripts are significantly overexpressed in ~72% of the available datasets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Our findings are consistent with previous clinical and preclinical studies, which demonstrated that MXD3 was highly expressed in neuroblastoma and medulloblastoma cells [30] , [31] , and it was associated with high-risk features [30] . In accordance with our findings, Ngo et al [32] reported that MXD3 alternative splicing is associated with the differential mRNA stability between splice variants with consequent pathogenic implications in GBM. In addition, MXD3 overexpression was shown to promote proliferation in mouse cerebellar granule neuron precursors (GNPs) [29] and negatively regulate differentiation in spleen-derived mouse B cells [33] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous clinical and preclinical studies, which demonstrated that MXD3 was highly expressed in neuroblastoma and medulloblastoma cells [30] , [31] , and it was associated with high-risk features [30] . In accordance with our findings, Ngo et al [32] reported that MXD3 alternative splicing is associated with the differential mRNA stability between splice variants with consequent pathogenic implications in GBM. In addition, MXD3 overexpression was shown to promote proliferation in mouse cerebellar granule neuron precursors (GNPs) [29] and negatively regulate differentiation in spleen-derived mouse B cells [33] .…”
Section: Discussionsupporting
confidence: 93%
“…MXD3 is highly expressed in neuroblastoma and medulloblastoma cell lines [30] , [31] , and it was associated with high-risk features [30] . A previous study has also implicated MXD3 alternative splicing in glioblastoma multiforme (GBM) [32] . In addition, MXD3′s overexpression was shown to promote proliferation in mouse cerebellar granule neuron precursors (GNPs) [29] , and to negatively regulate differentiation in mouse spleen-derived B cells [33] .…”
Section: Introductionmentioning
confidence: 97%
“…These results suggest that MXD3 is an anti-apoptotic factor ( Yoshida et al, 2020 ). Furthermore, the anti-apoptotic function of MXD3 has been identified in glioblastoma ( Ngo et al, 2019 ) and B-cell acute lymphoblastic leukemia ( Barisone et al, 2015 ). As a targeted therapeutic site, MXD3 enhances the killing of cancer cells and reduces the toxicity suffered by normal cells ( Satake et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al found that 10 hub genes, including MXD3, were aligned with HCC progression based on a gene co-expression network analysis [ 14 ]. Moreover, Ngo et al also found that, across the datasets, MXD3 was highly overexpressed in HCC with a 2.88-fold change in relation to normal tissues [ 10 ]. The MXD3 promoter sequence region has a tendency to be hypomethylated in liver cancer in respect to adjacent tissue samples [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression levels of MXD3 have been seen in numerous cancers. Previously, MXD3 overexpression was detected to elevate in glioblastoma [ 10 ], medulloblastoma [ 11 ], acute lymphoblastic leukemia cell proliferation [ 12 ], renal cell carcinoma [ 13 ], and hepatocellular carcinoma (HCC) [ 14 ]. These varying results relate to the functions of MXD3 imply tissue-specific or pathophysiological roles of MXD3, depending on different tissues and developmental stages.…”
Section: Introductionmentioning
confidence: 99%